Parametric Study of Ultra-Wideband Dual Elliptically Tapered Antipodal Slot Antenna - Xianming Qing; Zhi Ning Chen; Michael Yan Wah Chia (International Journal of Antennas and Propagation)
Parametric study of the impedance and radiation characteristics of a dual elliptically tapered antipodal slot antenna (DETASA) is undertaken in this paper. Usually, the performance of the DETASA is sensitive to the parameters, the effects of major geometry parameters of the radiators and feeding transition of the DETASA on antenna performance are investigated across the frequency range of 1–18 GHz. The information derived from this study provides guidelines for the design and optimization of the DETASAs which are widely used for UWB applications.